Distributed collaborative system of product designing and manufacturing based on grid services. Issue 2 (25th February 2010) - Sun, C.L.; Gao, H.; Guo, D.M.
A distributed collaborative system based on grid services is proposed in this paper to support collaborative designing and manufacturing of products. The base of this system is an abstract model of collaborative designing and manufacturing. Resources are encapsulated into service objects and then the integration and sharing of these distributed heterogeneous resources are realised by using service proxy and open grid services architecture (OGSA). Services and interfaces of resources are described by extensible markup language (XML). The publishing and discovery of services are realised by utilising standardisation rule and similar vector matching technology. Lastly, the practicality of this system is validated by its application in the designing and manufacturing process of a product.